2020
DOI: 10.1039/d0sm01043j
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in creating complex and multiplexed surface-grafted macromolecular architectures

Abstract: Surface-grafted macromolecules, including polymers, DNA, peptides etc., are versatile modifications to tailor the interfacial functions in a wide range of fields. In the review, we aim to provide an overview...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 210 publications
0
5
0
Order By: Relevance
“…In particular, functionalization of slippery surfaces with responsive polymer grafting could provide a route towards smart, biomimicking surfaces with dynamically tunable interfacial interactions. [ 63 ] Recently, PDA has been found to initiate photopolymerization and facilitate polymer grafting, in which it serves as a radical generator under UV irradiation. [ 64 ] Utilizing this feature, a vast range of stimuli‐responsive polymers could be grafted to functionalize the slippery LPDMS surface using the PDA patterns as templates ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, functionalization of slippery surfaces with responsive polymer grafting could provide a route towards smart, biomimicking surfaces with dynamically tunable interfacial interactions. [ 63 ] Recently, PDA has been found to initiate photopolymerization and facilitate polymer grafting, in which it serves as a radical generator under UV irradiation. [ 64 ] Utilizing this feature, a vast range of stimuli‐responsive polymers could be grafted to functionalize the slippery LPDMS surface using the PDA patterns as templates ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the integration of different polymer brush types in a single system allows for the creation of multifunctional surfaces. [ 38 ] Huang et al. [ 39 ] have developed a mixed rod‐coil brush system with poly(N‐isopropylacrylamide) (PNIPAM)/poly(γ‐benzyl‐l‐glutamate) and shown that more well‐defined end‐point functional nanospikes can be achieved by incorporating secondary brushes into the system.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the integration of different polymer brush types in a single system allows for the creation of multifunctional surfaces. [38] Huang et al [39] have developed a mixed rod-coil brush system with poly(N-isopropylacrylamide) (PNIPAM)/poly(𝛾-benzyll-glutamate) and shown that more well-defined end-point functional nanospikes can be achieved by incorporating secondary brushes into the system. Zhao et al [40] have reported successful fabrication of multiplexed brush architectures and reported the precise regulation of biomolecule immobilization using poly (glycidyl methacrylate)/poly(2-(2-azido-2-methyl-1-oxopropoxy) ethyl methacrylate) brush-based patterned surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer brushes (PBs) consist of polymer chains that are densely tethered to a surface by one end . Surface modification through polymer brushes has become a powerful tool due to the high degree of synthetic flexibility on various substrates including metal, glass, and polymer surfaces. PBs enable the obtainment of functional coatings with well-controlled composition, architecture, and thickness. Polyelectrolyte brushes (PEBs), which contain charged groups in their repeating units, constitute an important class of PBs . They exhibit distinctive properties due to the repulsive electrostatic and steric interactions; those can be adjusted by counterions, pH, salt concentration, and solvent quality. Many applications have been described for PEBs including artificial joints, enzyme immobilization supports, , smart actuators, , and responsive interfaces .…”
Section: Introductionmentioning
confidence: 99%